Binary Atomically Dispersed Metal‐Site Catalysts with Core−Shell Nanostructures for O2 and CO2 Reduction Reactions. Issue 10 (5th August 2021) - Yang, Xiaoxuan; Wang, Maoyu; Zachman, Michael J.; Zhou, Hua; He, Yanghua; Liu, Shengwen; Zang, Hong-Ying; Feng, Zhenxing; Wu, Gang
Abstract : Engineering atomically dispersed metal site catalysts with controlled local coordination environments and 3D nanostructures effectively improves the catalytic performance for the oxygen reduction reaction (ORR) and the carbon dioxide reduction reaction (CO2 RR), which are critical for clean energy conversion and chemical production. Herein, an innovative approach for preparing core−shell nanostructured catalysts with different single‐metal sites in the core and the shell, respectively, is developed. In particular, as the shell precursors, covalent organic polymers with a thin layered structure that is polymerized in situ and coated on a metal‐doped ZIF‐derived carbon core are used, followed by a controlled thermal activation. The selective combination and construction of different metal sites increase active site density in the surface layers, promote structural robustness, facilitate mass/charge transfer, and yield a possible synergy of active sites in the core and the shell. The p‐FeNC(shell)@CoNC(core), consisting of a polymerized FeTPPCl‐derived carbon layer (p‐FeNC) on a Co‐doped ZIF‐derived carbon (CoNC), exhibits remarkable ORR activity and stability in acidic media along with encouraging durability in H2 –air fuel cells. Likewise, a p‐FeNC(shell)@NiNC(core) catalyst demonstrates outstanding CO2 RR activity and stability. Hence, integrating two appropriate single‐metal sites in core and shell precursors, respectively, can modulate morphological and catalytic properties for a possible synergy toward different electrocatalysis processes. Abstract : An effective synergistic catalysis strategy is developed to obtain atomically dispersed dual‐site catalysts with a core−shell architecture by allocating different isolated sites on the core and shell part via a step‐by‐step self‐assembly method, realizing different single‐site functionalizations. The unique method is versatile in regulating different catalytic activities by controlling the active sites of different building units.